Digital Branding Model Pada Pengembangan Ekonomi Kreatif UMKM Kain Songket Pringgasela Kabupaten Lombok Timur - Rayie Tariaranie Wiraguna; Nur Anita Yunikawati; Retno Sulistiyaningsih (Pusat Riset dan Inovasi Nasional, 2023)
Pringgasela Village is one of the villages in East Lombok district with songket cloth MSMEs with a cultural heritage that has been preserved to this day. Several groups of Songket cloth MSMEs in Pringgasela Village are well known to various corners and are always used as a reference for tourists when visiting Lombok Island. As a creative industry, songket cloth MSMEs cannot be separated from the impact of the COVID-19 pandemic in 2020. Various problems arose due to the COVID-19 pandemic, and as a result, not a few MSME players in Pringgasela village went out of business. The local government, together with related sectors, continues to strive to stimulate the economy of the people in the village so that it can revive and develop further. The development of digital technology allows businesses to market their products online and use transactions through the online banking system. Digital technology development has changed the paradigm of MSME marketing, which is carried out conventionally digitally by utilizing social media, e-commerce, and websites as a medium for branding and marketing. Using digital/online media is the right choice for MSME players to expand their network and business reach.